Chemical Synthesis and Characterization of Ce0.8Y0.18Ca0.02O1.89 as Electrolyte for Solid Oxide Fuel Cells - Tian, Changan; Bao, Weitao; Cheng, Jihai; Yin, Qiyi; Zhao, Difang; Wang, Yu; Wu, Fan (Asian Journal of Chemistry, 2012)
The synthesis of nano-sized Ce0.8Y0.18Ca0.02O1.89 (YCDC) powders by citrate gel route has been investigated. The details of gel's combustion were investigated by TG-DSC and the structure of as-synthesized powders from auto-combustion was characterized by XRD. The results show that single phase YCDC powders with average size of 50 nm can be synthesized by citrate gel route. The as-synthesized powders exhibited high sinter activity, it can be sintered to 95 % of its theoretical density at 1250 ºC for 4 h. The YCDC composition exhibits a total conductivity of 0.02 S/cm at 700 ºC.